The Role of Metacognitive Processes and Emotional Schemas in Obsessive Compulsive Disorder - Sevinc ULUSOY; Kaasim Fatih YAVUZ; Tugba KARA; Mehmet Emrah KARADERE (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi, 2015)
Objective: This research aims to investigate the relationship between disorder severity and ruminative thinking style, emotional schemas, thought-action fusion and reciprocal interaction of these variables at individuals with obsessive compulsive disorder(OCD). Method: The sample of the study consists of 18 male and 47 female individuals who diagnosed as OCD according to DSM-IV-TR that applied the outpatient clinic of Bakirkoy Research Hospital for Psychiatry and Neurology between September 2014 and April 2014. Sociodemographic form, Yale Brown Obsessive Compulsive Scale (YBOCS), Ruminative Thinking Style Questionnaire (RTSQ), Thought Action Fusion Scale (TAFS) and Leahy Emotional Schema Questionnaire (LESQ) were applied to participants. Data analyzed by using SPSS 20 version. Results: The mean age of participants is 31,80±7,41. According to results determined by using Pearson Correlation Analysis, a significant positive correlation between RTSQ total scores and LESQ weakness against emotions, acceptance of feelings, duration sub-scales, TAFS likelihood sub-scale, YBOCS obsession, YBOCS compulsion and YBOCS total scores was found. Also according to multiple linear regression analysis; its determined that RTSQ total scores predict YBOCS obsession, YBOCS compulsion and YBOCS total scores, TAFS Moral sub-scale total scores predict only YBOCS obsession total scores. Conclusion: It can be suggested that treatment objectives at psychotherapy approaches for OCD should involve ruminative response style and TAF Moral dimension when all the results evaluated together. While emotional schemas dont predict OCD severity directly, emotional schemas can have indirect effects on severity of disorder when the correlation between other scales considered. [JCBPR 2015; 4(3.000): 173-183]